Price behaviour of coconut and coconut products in India - Jaisal Babu N (Department of Agricultural Economics, College of Horticulture, 2005)
The coconut-based industry in India revolves around the price behaviour of coconut oil, which in turn depends on the price and overall availability of other vegetable oils. It is against this background that the study entitled "Price behaviour of coconut and coconut products in India" was undertaken with the specific objective to study the secular trend, seasonality and irregular movements in the price of coconut and major coconut products in India, and to assess the implications of liberalized exim policies. The study was conducted during the year 2004-05, using secondary data. It was found that an exponential growth model gave the best fit for area and production of coconut where as a quadratic form turned out to be the best fit for yield. The analysis showed that the area and production in the long run exhibited an increasing trend, while the productivity was highly fluctuating . • There was a clear shift in the export basket of coconut products, with coconut • oil cake being the major item exported in the sixties, which is now occupied by coconut oil and coir products. Similarly, copra was the major item of import in the sixties, which is now occupied by coconut oil. The price behaviour of coconut and its• products were studied using the , . classical time series analysis. The prices of coconut, copra and coconut oil had a tendency to increase in the long run. The domestic price of copra and coconut oil was higher than the international price during theperiod under study, The domestic markets were well integrated for coconut products under consideration on the one hand, with the international market on the other hand.